2007
DOI: 10.1016/j.jhep.2006.11.017
|View full text |Cite
|
Sign up to set email alerts
|

R-Etodolac decreases β-catenin levels along with survival and proliferation of hepatoma cells

Abstract: Background-Inhibition of hepatoma cells by cyclooxygenase (COX)-2 dependent and independent mechanisms has been shown previously. Here, we examine the effect of Celecoxib, a COX-2-inhibitor and R-Etodolac, an enantiomer of the nonsteroidal anti-inflammatory drug Etodolac, which lacks COX-inhibitory activity, on the Wnt/β-catenin pathway and human hepatoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…Cieply et al [20] noticed that the overexpression of GS is highly correlated with b-catenin mutation and proposed GS as an overall reliable marker of b-catenin activation secondary to its mutation. Behari et al [21] proposed that targeting b-catenin might be an attractive approach to HCC treatment. Luca DT et al suggested that, in keeping with this early role in hepatic tumorigenesis, GS overexpression did not associate with tumor dedifferentiation [22], which is confirmed by the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Cieply et al [20] noticed that the overexpression of GS is highly correlated with b-catenin mutation and proposed GS as an overall reliable marker of b-catenin activation secondary to its mutation. Behari et al [21] proposed that targeting b-catenin might be an attractive approach to HCC treatment. Luca DT et al suggested that, in keeping with this early role in hepatic tumorigenesis, GS overexpression did not associate with tumor dedifferentiation [22], which is confirmed by the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…In liver tumor cells, we have found that targeting ␤-catenin with an experimental drug, R-Etodolac, leads to decreased proliferation and survival of two human hepatoma cell lines (HepG2 and Hep3B). 56 This drug is an enantiomer of Etodolac, an NSAID used in inflammatory diseases of the joints. REtodolac lacks any cox-inhibitory activity or its notorious side effects and is already in phase II trials for refractory chronic lymphocytic leukemia.…”
Section: Wnt/␤-catenin In Hepatic Tumorsmentioning
confidence: 99%
“…It has been shown that pharmacologic inhibition of -catenin decreases survival of hepatoma cells (Behari et al, 2007). Inactivation of -catenin suppressor APC led to spontaneous development of HCC in a mice model, suggesting the direct contribution from activated Wnt signaling to hepatocarcinogenesis (Colnot et al, 2004).…”
Section: Wwwintechopencommentioning
confidence: 99%